The mining industry and the environment - Milla Lostaunau, Luis (2000)
In this period of its history , humanity building on the achievements of scientific and technical progress has played and mastered the use of the Ocean and the Cosmos. At the time it was evident that some types of human activity impact negatively on the environment and their consequences will be disastrous in the future. Every time we realize that humanity can not and should not thoughtlessly use its enormous power , not breaking into nature on a limited scale and radically remake without complying with the possible negative consequences of economic activity. The more transformations occur in natural resources, can not be neglected the effects of change occurring in the biosphere as a result of productive activity . Depth studies of the ecological situation indicate that continue to influence unilaterally and spontaneously considerably in the same degree , humanity could make our civilization in a purely technicist creature who not only transformed deserts into oasis but also what that was what become desert oasis and threatens to kill all life on earth. The problem of environmental pollution and other negative impacts of the economic activity of man on earth, reaches the size of the spontaneous influx of men over nature, in cooperation with it in a conscious , oriented and planned. Many ecologists believe that there is widespread losses throughout the world, are the main ecological and social problem. Therefore, man is the main pollutant of the environment through the processes that are related to their daily lives, their productive activity and comfort. In all these processes, solid, liquid and gaseous wastes that eventually will contaminate nature are generated . In the case of Peru is a purely mining country , from colonial times , where and minerals, especially precious metals were mined , it has been polluted in the easiest places to drain the tailings , such as rivers , a current special case is given in the Central region , where the Centromin Peru Mining Company , for many years it has been polluting the Mantaro river , this river is quite plentiful and supplies water to the region for irrigation and other activities, however due to the amount of chemicals that are thrown has polluted the watershed, it can be appreciated on several tens of kilometers, by its reddish color, the same as it is not used by people just for the danger of seriously affect the plants and animals, even humans.